STUDENTS’ MOTIVATION IN LEARNING ENGLISH LANGUAGE (A CASE STUDY OF ELECTRICAL ENGINEERING DEPARTMENT STUDENTS) - Anna Riana Suryanti Tambunan; Tiarnita M. S Siregar (English Department - University of Sultan Ageng Tirtayasa, 2016)
The real challenges for teachers and learners lie in finding ways of sustaining the motivation through the long and often arduous process of learning a language. The aim of this study was to describe the students’ instrumental and integrative motivation in English language learning. A case study was used in this study by distributing the motivation questionnaire to the 36 second-year students of English Department at Sultan Ageng Tirtayasa university in Serang, Banten. Then, the data from the returned questionnaire were analyzed by describing the types of motivation the students use. Findings from this study indicated that the second year students were instrumentally motivated and their integration was sufficient, too. The instrumental motivation was found to have more impact on students than integrative one. Three interrelated instrumental motivations in studying English were identified: future study, scores and career. In addition the students mentioned that good marks in English were required for their future studies and a good qualification for their careers. In conclusion, motivation has a contribution towards the students’ English language learning. The findings could be useful for researchers and teachers in improving students’ English language learning by conducting effective teaching and learning strategies to develop the students’ motivation. Key words: instrumental motivation; integrative motivation; motivation